Research-Creation and More-Than-Human Collaboration - Confente, Oriana (Imaginations)

(untitled) (York University, 2024)
This is a set of guiding principles for more-than-human collaboration in research-creation. As slippery terms with unclear boundaries, we must form practical and theoretical protocols to navigate multispecies activities that benefit the emerging episteme. To design inclusive frameworks for artistic experimentation, we must recognize other-than-humans as contributors rather than objects of study. Key concepts are established around valuing difference, agency, and care within postnatural arrangements to decentre the “human” in “more-than-human.” These principles are applicable to students, scholars, artists, makers, practitioners, and anyone else engaging with research-based art.